Asymptotic behavior of periodic solutions in one-parameter families of Liénard equations. (January 2020) - Cardin, Pedro Toniol; Novaes, Douglas Duarte
Abstract: In this paper, we consider one-parameter ( λ > 0 ) families of Liénard differential equations. We are concerned with the study on the asymptotic behavior of periodic solutions for small and large values of λ > 0 . To prove our main result we use the relaxation oscillation theory and a topological version of the averaging theory. More specifically, the first one is appropriate for studying the periodic solutions for large values of λ and the second one for small values of λ . In particular, our hypotheses allow us to establish a link between these two theories.